The Relationships Between Organizational Citizenship Behavior, Affective Commitment and Team Effectiveness in A Non-Profit Organization - Siti Norain Binti Abd Samad; Ridhawati Zakaria; Norashikin Hussein; Noor Azura Dahalan; Dayang Nailul Munna Abg Abdullah (Information Management and Business Review, 2024)
Non-profit organizations play a crucial role in fostering healthy communities by providing vital services that contribute to economic stability and mobility. However, the effectiveness of these organizations hinges on the positive and engaged behavior of their employees. These organizations may face challenges in staffing and resource management that can hinder performance and funding, making team effectiveness and organizational citizenship behavior essential for success. This study investigates the relationships between organizational citizenship behavior (OCB), affective commitment, and team effectiveness in a non-profit organization based in Selangor. Utilizing a cross-sectional design and a quantitative approach, 118 employees across local and international branches of a non-profit organization participated in an online survey. Data analysis was conducted using SPSS version 26. The study found that conscientiousness, courtesy, and civic virtue are the dimensions of (OCB) that positively influence team effectiveness, while altruism and sportsmanship did not show a significant impact in the non-profit context. Conscientious employees who are diligent and responsible, along with those who exhibit courtesy by being considerate and communicative, and those who actively participate in organizational activities, contribute meaningfully to team success. Furthermore, affective commitment, or employees' emotional attachment and identification with the organization, was also found to enhance team effectiveness, highlighting the role of an engaged and committed workforce in driving positive outcomes.